A COMPARISON OF LEARNING MANUFACTURING ENGINEERING DRAWINGS WITH INTERACTIVE MEDIA AND PRESENTATIONS MEDIA: (A Study on the Implementation of Vocational High School Curriculum) - C. Rudy Prihantoro (International Journal of Advanced Science and Technology, 2020)
This study aims to determine the increase in learning outcomes in Manufacturing Engineering Drawing subjects using interactive learning media compared to using presentation media in grade XI Machining, Vocational High School in Jakarta which applies the 2013 Vocational High School Curriculum. The research used a Quasi Experimental research model with a Non-Equivalent Control Group Design using pretest and posttest. The students enrolled in this research were divided into experimental group and control group. The control group members were taught using presentation media whereas the experimental group used interactive learning media. The results of this study obtained an increase in learning outcomes in the cognitive and psychomotor domains. It is found the average outcomes of the posttest in the cognitive dominion of the experimental group 82.59 greater than in the control group of 78.14 and there was an increase in learning outcomes from pretest to posttest by 72.5% for the experimental group and 63.8% for the control group. Psychomotor domain of the average scores in the experimental group is greater than the control group that is equal to 76.04 and 38.31.